Plasma microRNA-720 may predict prognosis and diagnosis in glioma patients - Chen, Peng (Biosci Rep, 2020)
We enrolled 122 patients with glioma who received surgery treatment in our hospital from June 2010 to May 2012, and 60 healthy individuals. We found that the plasma miR-720 in the glioma group was significantly higher than that in the healthy control group (3.19 ± 1.26 vs 0.98 ± 0.65, P<0.001). The sensitivity and specificity were 71.3% (95%CI: 62.4–79.1%) and 83.3% (71.5–91.7%), respectively. The results indicated that the plasma miR-720 level was associated with tumor grade (t = 104.418, P<0.001). The advanced tumor tended to have higher miR-720 expression level. No significant association was found between miR-720 and age, sex, tumor size, KPS and tumor position (P=0.438, 0.514, 0.518, 0.058, 0.226). The multivariate cox analysis indicated that the high expression of miR-720 (HR = 1.48, 95%CI: 1.12–2.97, P=0.023) was independently predictors of adverse prognosis in patients with glioma. The high expression of miR-720 was also associated with recurrence or development in patients with glioma (HR = 1.47, 95%CI: 1.18–3.14, P=0.012). Plasma miR-720 has a moderate diagnostic ability in early diagnostic of glioma and may be a potential tumor biomarker. The high plasma miR-720 was related to adverse prognosis in patients with glioma and could be a prognosis predictor of glioma patients.